Construção de um serviço de gerenciamento da Terapia Medicamentosa na atenção primária à saúde no SUS: um projeto de extensão universitária - Danielle Fernandes da Silva (2015)
The large consumption of medicines in society culminated in the emergence of a new social need: the need of a professional responsible for detecting, resolving and preventing drug-related problems. Medication Therapy Management (MTM) services use the theoretical framework of the practice of pharmaceutical care and can be seen as a possible solution to meet this demand. Studies have demonstrated favorable results from these services that justify its implementation at health care systems. In Brazil, partnerships between universities and the health systems have been established to promote the construction of MTM. Thus, the experiences of professional and graduate pharmacy students during the process of providing MTM services as a university extension activity may provide information that encourage the provision of this new health service. Thus, the aim of this study was to understand the construction process of MTM services in Primary Heath Care (PHC), through the experience of those involved. The methodology utilized was autoethnography. Ten semi-structured interviews were conducted. In addition, the researcher's field notes and the transcription of the meetings held between all participants were used. The results revealed aspects about the MTM service construction experience in PHC, especially about the partnership between the university and the health service. Themes concerning the pharmacist's job in PHC also emerged, like the real versus the ideal and the clinical role at pharmacys mercy. In the "autonomy and limitations in professional activities" are addressed some factors that interfere with clinical practice and consequently on its results. On "experiences in mentoring students during the construction of the GTM service", is carried an account of the experiences of take the tutoring simultaneously to the planning service. In vocation to care, issues and feelings of the researcher and the MTM team where discussed regarding the mission of taking responsibility for patients drug therapy. The PHC is a promising scenario for the construction of MTM services; however, questions about the pharmacists job organization and changes in the partnership between university and health systems should be further discussed. There is a need to systematize clinical pharmaceutical practice PHC and MTM provides the necessary tools for this reorganization. Discussion and reflection on how to insert PHC are critical to advance the work of this professional and improve health outcomes in this scenario in the unified health system.